Research on Frequency Dividing Control Strategy for Active Power Filter - 关维德; 黄小庆; 邓名高; 陈岗; 金维宇 (Kongzhi Yu Xinxi Jishu)
As traditional PI control strategy of output current control algorithm for active power filter (APF) has larger steady-state error, this paper proposes a novel frequency dividing control strategy. Detailed analysis of principles and implementation methods of the frequency dividing control strategy are given. Matlab simulation model is then established to analyze the effects of the two control strategies. Finally, an actual experiment is made to prove the excellent performance of the strategy. Simulation and actual experiment results show that the frequency dividing control strategy can improve the current control accuracy and compensation effect of APF.